DEVELOPMENT OF ANDROID-BASED NUMBER JUMPING ATHLETICS LEARNING MODULE (LONG JUMP, TRIPLE JUMP, POLE JUMP, HIGH JUMP) - Benny Aprial Simangunsong; Hardodi Sihombing (Journal Physical Health Recreation (JPHR), 2022)
This study aims to develop an android-based module for the theory and practice courses of athletics jumping numbers for students of the health and recreation physical education study program. The method used in this study is the research and development method from brog and gall. This development resulted in a product in the form of a research-based module in athletic theory and practice courses. the results of the analysis of the research data were in the form of content expert assessment (athletics courses) with a percentage of 85.64%, linguists with a percentage of 79.80%, validation results for learning media experts with a percentage of 88.65%, assessment results phase I trials (small group) with a percentage of 79.94%, results of the assessment of phase II trials (large group) with a percentage of 85.58%, results of field tests with a percentage of 92.15%, which means that this module is suitable for use as a teaching materials for the theory and practice of athletics course I for STOK Bina Guna students.